The prevalence of non-vascular pulmonary manifestations in Takayasu's Arteritis patients: A Retrospective multi-centred Turkish cohort study - ALİBAZ ÖNER, FATMA; DİRESKENELİ, RAFİ HANER (TAYLOR & FRANCIS LTD, 2022)
Objectives Takayasu's arteritis (TAK) is a rare vasculitis characterized by inflammation of intermediate- to large-size arteries. Although pulmonary artery involvement (PAI) is an expected finding in some TAK patients, data on non-vascular pulmonary involvement (NVPI) are limited. We aimed to investigate the frequency of NVPI, including parenchymal infiltration, nodules/cavities, pleural effusion, and haemorrhage, in TAK. Method We assembled a retrospective cohort of TAK patients from nine tertiary centres in Turkey. The demographics and clinical characteristics of patients were extracted from medical records and the imaging findings were evaluated for pulmonary manifestations. Results As of January 2021, 319 TAK patients (female/male 276/43; mean age 42.4 +/- 13.5 years) were recruited. Eighty-two patients had cough and/or dyspnoea and four had haemoptysis as pulmonary symptoms. On computed tomography assessment, the overall frequency of NVPI was 7.2%; parenchymal infiltrations were present in 10 (3.1%), pleural effusion in eight (2.5%), nodules/cavities in six (1.9%), and pulmonary haemorrhage in four patients (1.3%). In the whole cohort, 10.3% of patients had pulmonary artery hypertension (PAH) and 5.6% had PAI. Among patients with PAH or PAI, the overall frequency of NVPI was significantly higher than in the rest of the group. Conclusions In this TAK cohort from Turkey, we observed NVPI in 7.2% of patients, with parenchymal infiltrations being the most common, followed by pleural effusion. Notably, NVPI was more frequent in patients with PAH or PAI. Although not as common as PAI, NVPI should be kept in mind, especially in TAK patients with PAH or PAI.
Keywords: INVOLVEMENT